Statistical analysis for the characterization of solar energy utilization and inter-comparison of solar radiation at two sites in Cyprus. (15th March 2017) - Pashiardis, S.; Kalogirou, S.A.; Pelengaris, A.
Highlights: Statistical analysis of global radiation. Monthly and diurnal variation of global radiation. Frequency distribution of global radiation. Relationship between global and other radiation parameters. Comparison of global radiation between two sites. Abstract: A statistical analysis and inter-comparison of the solar radiation at two sites in Cyprus representing two different climate regimes of the island (Athalassa-inland plain vs Larnaca-coastal location) covering the period January 2013–December 2015 is presented. Mean annual and mean monthly daily totals of the global, horizontal beam and diffuse radiation and their frequency distribution at both sites are computed and discussed. The values of skewness and kurtosis coefficients are used to define the frequency distribution type of the above radiation parameters on a monthly basis. The statistical analysis is extended to the daily clearness index ( KT ), diffuse ratio ( KD ), and the ratio of horizontal beam to global radiation ( KB, G ). Furthermore, the influencing factors on the magnitude of the radiation components were examined. The value of K T was used to classify three different types of days such as clear, partially cloudy and cloudy days. Then, a statistical analysis of the solar radiation components was performed. On an average annual basis, more than 80% of the days are classified as either clear or partially cloudy at both stations. Additionally, the influence of the atmospheric absorption and scattering of the solar radiation under clear skies was examined on the basis of the Linke turbidity factor ( T L ). The results of this analysis are used to characterize and compare the radiation regimes of the two sites. Both sites have relatively high intensity of global and direct horizontal radiation. The annual average daily global radiation intensity is 18.5 MJ m −2 at Athalassa and 19.9 MJ m −2 at Larnaca. The horizontal beam radiation is 13.1 MJ m −2 for Athalassa and 14.2 MJ m −2 for Larnaca. Therefore, the fraction of the beam component of the global radiation is comparatively high at both sites, as indicated by the annual average daily fraction which is greater than 0.600. Generally, Larnaca has slightly higher rates of global radiation than Athalassa, as indicated by the average yearly cumulative global irradiation which is 6763 MJ m −2 for Athalassa and 7274 MJ m −2 for Larnaca.